The metabolism of lean and fat hooded seal pups (Cystophora cristata): how fat contributes to the total metabolic rate - Evertsen, Agnete Pedersen (UiT Norges arktiske universitet, 2021)
Hooded seal pups are highly adapted to their proximate environment from the moment they are born. They are born with a substantial blubber layer, and they gain 20+ kg of body mass during their short nursing-period (2-4 days). With the body mass gained during nursing mainly being a result of fat deposition, it made them an excellent model to use when studying the fat metabolism and its contribution to the total metabolic rate. Indirect calorimetry was used through expired gas-analysis, using VCO2 as a proxy for the metabolic rate. We strived to include both lean, newborn pups and fat, weaned pups. Some of the pups lacked data on fat percentage, and others on body length, so fat percentage and condition index (CI = BM/BL) were predicted using linear regression models for hooded seals captured from 2007-2019 with these data. There were three standard measurement conditions: 1) They were within their thermoneutral zone, 2) They were post-absorptive and 3) They were sleeping. The results showed a significant negative relationship between the weight-specific sleeping metabolic rate (SMR) and body fat percentage (p =0.0039) using linear regression. A correlation was also found between the weight-specific SMR and condition index (CI = body mass/body length), with a significant negative relationship (p= 0.0021). In conclusion, this study found that fat is relatively inert and contributes less than the lean body mass (LBM) to the total metabolism.